Comparison Procedures of Determination Masking Curve for Audio Data Hiding Applications - Jarosław WOJTUŃ; Jarosław BUGAJ (Communications of International Proceedings, 2021)
Steganographic systems are used for the transmission of hidden data in the original signal. Imperceptibility of hidden information is a critical parameter of steganographic systems. The article describes and compares two ways to determine masking curve for audio steganography algorithms. We checked the quality of the signals after embedding data.
Keywords: Audio Steganography; Audio Watermarking; Psychoacoustic Model; Linear Predictive Coding; Signal To Mask Ratio